ANALISIS PERFORMA PEMASARAN PADA INDUSTRI KREATIF DI PEKANBARU (STUDI EMPIRIS PADA PUSAT OLEH-OLEH KHAS RIAU) - Arfah, Lita (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The goal of this research is to establish and build a conceptual model of marketing performance. This study’s specific aim is to investigate and analyze the relationship between entrepreneurial orientation and marketing performance, as well as the relationship between product innovation and marketing performance and the relationship between product differentiation and marketing performance. Purposive sampling is the sampling technique that was utilized, and the sample consisted of 30 entrepreneurs who run medium-sized creative firms and offer traditional Riau souvenirs. The authors of this study used interviews and questionnaire distribution to gather their data. The gathered data were then subjected to an analysis utilizing SPSS 26 methods. The study’s managerial findings, such as entrepreneurial orientation, product innovation, and differentiation that significantly impacted marketing performance, were added to the body of knowledge on how to create marketing performance